Դասական կիթառի պատմական զարգացման փուլերի հետազոտություն - Նունե Պողոսյան (ՀՀ ԳԱԱ հրատ.)
В данной статье собраны материалы по истории возникновения и становления гитарного искусства, что предоставляет возможность поэтапно изучить историю классической гитары. This article considers the origin and evolution of the guitar and provides an opportunity to explore the history of classical guitar through all of its stages of development.
Keywords: Music; Instrumental Techniques